2018
DOI: 10.1021/acsomega.8b00150
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Antibacterial Activity of Novel Symmetric Carbazole-Based Ethynylpyridine Photosensitizers

Abstract: In this study, two kinds of novel carbazole-based ethynylpyridine salts: 3,6-bis[2-(1-methylpyridinium)ethynyl]-9-pentyl-carbazole diiodide (BMEPC) and 3,6-bis[2-(1-methylpyridinium)ethynyl]-9-methyl-carbazole diiodide (BMEMC) have been employed as photosensitizers owing to their excellent antibacterial activity. These molecules possess symmetric A−π–D−π–A-type structures, which would bring in the unique optical properties. The inhibition zone measurement of a gradient concentration from 0 to 100 μM showed BME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Following on from the above-mentioned study, the same two carbazole-based ethynylpyridine salts, 9 and 10, were further utilized as photosensitizers for antibacterial studies. Their antibacterial activity was tested against Escherichia coli (E. coli) [117]. An antibacterial mechanism was proposed based on electron paramagnetic resonance characterization, which indicated that a nitride radical is generated upon laser irradiation.…”
Section: Small Molecule-based Saltsmentioning
confidence: 99%
“…Following on from the above-mentioned study, the same two carbazole-based ethynylpyridine salts, 9 and 10, were further utilized as photosensitizers for antibacterial studies. Their antibacterial activity was tested against Escherichia coli (E. coli) [117]. An antibacterial mechanism was proposed based on electron paramagnetic resonance characterization, which indicated that a nitride radical is generated upon laser irradiation.…”
Section: Small Molecule-based Saltsmentioning
confidence: 99%
“…The different activities are associated with the higher affinity of the longer alkyl chain to the cellular structure which yields a large accumulation of the molecules. In addition, the authors propose nitride radical formation upon light irradiation using EPR measurements and 5,5-dimethyl-1-pyrroline- N -oxide (DMPO) as the spin-trapping agent [ 75 ].…”
Section: Alkaloids In Photoinactivation Of Microorganismsmentioning
confidence: 99%
“…In recent years, bacterial resistance has increased significantly with the excessive use of antibiotics, which has led to a serious crisis of multidrug-resistant bacterial infections, and human health and safety have been threatened once again. , As a result, there is an urgent need to develop new antimicrobial channels to replace traditional antibiotic therapy. Photodynamic therapy (PDT) is a method to inactivate bacteria by producing reactive oxygen species (ROS), such as singlet oxygen ( 1 O 2 ), superoxygen, or hydroxyl radicals with the help of photosensitizers (PSs) under the common conditions of specific light and oxygen. , The obtained 1 O 2 causes irreversible damage to microbial cell membranes and plays a major role in photodynamic damage. , Moreover, due to the broad-spectrum antibacterial properties and nondrug resistance, PDT has been considered as a promising alternative for the replacement of traditional antibiotic therapy. , …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Moreover, due to the broad-spectrum antibacterial properties and nondrug resistance, PDT has been considered as a promising alternative for the replacement of traditional antibiotic therapy. 4,7 Ce6 has been widely used as a photosensitizer for the low dark toxicity and high ROS yield, which exhibits ideal antibacterial PDT performance. 7 Ce6 has good absorption in the near-infrared wavelength range 600−900 nm, which possesses tissue penetration ability due to the longer wavelengths of light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation